Comparing Patients' Opinions on the Hospital Discharge Process Collected With a Self-Reported Questionnaire Completed Via the Internet or Through a Telephone Survey: An Ancillary Study of the SENTIPAT Randomized Controlled Trial - Couturier, Berengere; Carrat, Fabrice; Hejblum, Gilles (JMIR Publications, 2015)
BackgroundHospital discharge, a critical stage in the hospital-to-home transition of patient care, is a complex process with potential dysfunctions having an impact on patients' health on their return home. No study has yet reported the feasibility and usefulness of an information system that would directly collect and transmit, via the Internet, volunteer patients' opinions on their satisfaction concerning the organization of hospital discharge. ObjectiveOur primary objective was to compare patients' opinions on the discharge process collected with 2 different methods: self-questionnaire completed on a dedicated website versus a telephone interview. The secondary goal was to estimate patient satisfaction. MethodsWe created a questionnaire to examine hospital discharge according to 3 dimensions: discharge logistics organization, preplanned posthospital continuity-of-care organization, and patients' impressions at the time of discharge. A satisfaction score (between 0 and 1) for each of those dimensions and an associated total score were calculated. Taking advantage of the randomized SENTIPAT trial that questioned patients recruited at hospital discharge about the evolution of their health after returning home and randomly assigned them to complete a self-questionnaire directly online or during a telephone interview, we conducted an ancillary study comparing satisfaction with the organization of hospital discharge for these 2 patient groups. The questionnaire was proposed to 1141 patients included in the trial who were hospitalized for ≥2 days, among whom 867 eligible patients had access to the Internet at home and were randomized to the Internet or telephone group. ResultsOf the 1141 patients included, 755 (66.17%) completed the questionnaire. The response rates for the Internet (39.1%, 168/430) and telephone groups (87.2%, 381/437) differed significantly (P<.001), but their total satisfaction scores did not (P=.08) nor did the satisfaction subscores (P=.58 for discharge logistics organization, P=.12 for preplanned posthospital continuity-of-care organization, and P=.35 for patients' impressions at the time of discharge). The total satisfaction score (median 0.83, IQR 0.72-0.92) indicated the patients' high satisfaction. ConclusionsThe direct transmission of personal health data via the Internet requires patients' active participation and those planning surveys in the domain explored in this study should anticipate a lower response rate than that issued from a similar survey conducted by telephone interviews. Nevertheless, collecting patients' opinions on their hospital discharge via the Internet proved operational; study results indicate that conducting such surveys via the Internet yields similar estimates to those obtained via a telephone survey. The results support the establishment of a permanent dedicated website that could also be used to obtain users' opinions on other aspects of their hospital stay and follow-up. Trial RegistrationClinicaltrials.gov NCT01769261; http://clinicaltrials.gov/ct2/show/NCT01769261 (Archived by WebCite at http://www.webcitation.org/6ZDF5bdQb).